2014
DOI: 10.1126/science.1256679
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding to the FeMo-cofactor: Structures of CO-bound and reactivated nitrogenase

Abstract: The mechanism of nitrogenase remains enigmatic, with a major unresolved issue concerning how inhibitors and substrates bind to the active site. We report a crystal structure of carbon monoxide (CO) inhibited nitrogenase MoFe-protein at 1.50 Å resolution, revealing a CO molecule bridging Fe2 and Fe6 of the FeMo-cofactor. The μ2 binding geometry is achieved by replacing a belt-sulfur atom (S2B) and highlights the generation of a reactive iron species uncovered by the displacement of sulfur. The CO inhibition is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
465
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 375 publications
(491 citation statements)
references
References 44 publications
15
465
1
10
Order By: Relevance
“…Strikingly, the signal intensities of these samples displayed a linear correlation with the amounts of CO released from them ( Fig. 3C), firmly establishing CO as the origin of the unique EPR To carry out experiments on the catalytic competence of the CO-bound conformations, the VFe protein was loaded with 12 CO or 13 CO in the presence of Eu II -DTPA, reisolated from the CO atmosphere, and subjected to turnover conditions upon addition of Fe protein and ATP in the presence of dithionite. EPR analysis revealed that the VFe protein preloaded with 12 CO (Fig.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Strikingly, the signal intensities of these samples displayed a linear correlation with the amounts of CO released from them ( Fig. 3C), firmly establishing CO as the origin of the unique EPR To carry out experiments on the catalytic competence of the CO-bound conformations, the VFe protein was loaded with 12 CO or 13 CO in the presence of Eu II -DTPA, reisolated from the CO atmosphere, and subjected to turnover conditions upon addition of Fe protein and ATP in the presence of dithionite. EPR analysis revealed that the VFe protein preloaded with 12 CO (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…2A) (12). Electron paramagnetic resonance (EPR) analysis of this CO-bound MoFe protein identified a CO-derived signal (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Preservation of these features may be crucial for the reactivity of Fe 6 RHH , as a recent crystallographic study revealed displacement of a "belt" S atom by a CO moiety upon binding of CO to the M-cluster, [22] an event requiring the presence of the interstitial C atom to maintain the structural integrity of the M-cluster when the S "belt" undergoes significant rearrangement during catalysis. Thus, by analogy, the equivalents to the "belt" S and "central" C atoms in Fe 6 RHH may render it capable of interacting with substrates in an analogous manner to that of the M-cluster; in particular, such an analogy could explain the reactivity of Fe 6 RHH toward CN − , which parallels the reactivity of the Mcluster toward CO (an isoelectronic molecule to the CN − ion), in reductive C-C coupling.…”
Section: Introductionmentioning
confidence: 99%